A pragmatic lifestyle intervention for overweight and obese women with gestational diabetes mellitus (PAIGE2): A parallel arm, multicenter randomized controlled trial study protocol - McAuley, Emma; Fleck, Olwen; Cassidy, Laura; Kemp, Bridie J.; Cupples, Gina; Kelly, Bronagh; Creighton, Rachel M.; Graham, Una; Wallace, Helen; Patterson, Chris C.; McCance, David R. (Frontiers in Clinical Diabetes and Healthcare, 2023)
The global epidemic of type 2 diabetes and obesity has been translated into pregnancy, with up to 18% of women being diagnosed worldwide with Gestational Diabetes Mellitus (GDM). Whilst preventive strategies have proven effective in the non-pregnant context, attrition rates are high and there is an urgent need to develop a customized, pragmatic lifestyle intervention for women both during and after pregnancy. Diet and exercise modification, behavioral support, and Commercial Weight Management Organizations have been strongly recommended to aid postpartum weight reduction for mothers with previous GDM, subsequently reducing their risk of developing obesity and type 2 diabetes. This study, informed by a previous pilot study, aims to determine the effectiveness of a pragmatic pregnancy and postpartum lifestyle modification program for overweight/obese women with GDM (PAIGE2) to reduce body weight at 12 months postpartum. This is the protocol for the PAIGE2 study, developed based on results from a pilot study (PAIGE). A six center, two parallel arm, 12-month, randomized controlled trial will be conducted across Northern Ireland and the Republic of Ireland (3 centers each), involving 340 women with GDM and body mass index >25 kg/m2 recruited during pregnancy. The lifestyle intervention involves a one-hour virtual educational program (to take place at 32-36 weeks gestation). Postpartum, the intervention will include monthly phone calls, weekly motivational text messages, weekly step counts, and referral for three months to a Commercial Weight Management Organization (Slimming World). The control arm will receive usual care as offered by the local maternity hospital. The primary outcome is weight loss at 12 months postpartum. Study visits for anthropometric and clinical measurements, fasting blood samples, questionnaires pertaining to health, wellbeing and physical activity will take place at 6 weeks, 6- and 12-months postpartum. Focus groups will be conducted with intervention mothers’ post-intervention to determine the acceptability of the study design including utility of Slimming World, feasibility of remote patient contact, family involvement and patient satisfaction. The PAIGE2 study will address gaps in previous research and, if positive, has the potential to have major public health implications for the prevention of future GDM and subsequent type 2 diabetes. ClinicalTrials.govIdentifier:NCT04579016